Effect of locality on carotenoids stability in Malaysian orange sweet potato (Ipomoea batatas) tuber flesh - Kammona, Suhair; Othman, Rashidi; Jaswir, Irwandi; Jamal, Parveen (INSI Publications, 2015)
arotenoids are bioactive antioxidant pigments with pharmaceutical potential. Carotenoids such as α-carotene and β-carotene react as provitamin A in human body, while lutein and zeaxanthin are two major components of the macular pigment of the retina. Due to its high carotenoids and pro-vitamin A content, sweet potato (Ipomoea batatas) is believed to have many nutritional and medicinal benefits. The carotenoid content in sweet potato or as locally known Keledek in Malaysia were determined using spectrophotometry and high performance liquid chromatography HPLC analysis. Objective: This study aimed to assess the carotenoids content stability in five different localities in Malaysia (Kelantan, Pahang, Terengganu, Selangor and Perak) of orange sweet potato tuber. All analyses were carried out in triplicate. Results: Results of this study revealed that the orange sweet potato (OSP) from Kelantan showed the highest total carotenoids content. For individual carotenoids, β-carotene ranged from 1123.85±0.04 μg/g to 399.4±3.62 μg/g DW. Zeaxanthin was detected only in Kelantan OSP 13.01±0.00 μg/g DW. Carotenoids profiles for orange fresh tubers from five Malaysian localities revealed marked differences in individual carotenoids composition. Conclusion: Generally, location or geographic site of crop can be considered as an important factor that affects carotenoids content in sweet potato flesh tuber.